Integration of nanophotonic devices on silicon - Di Meo, Valentina; Crupi, Felice; Cocorullo, Giuseppe; Rendina, Ivo; Esposito, Emanuela (My University, 2019)
The purpose of this thesis research project has been the integration of photonic nanostructures on silicon substrate. In particular, three different devices have been developed, whose application fields fall within the main research topics of silicon photonics. Indeed, a plasmonic biochemical sensor, an all-dielectric metamaterial for all-optical switching applications and a 1D photonic crystal as an interconnecting device have been successfully integrated on silicon substrate. All of the proposed devices could lead to noticeable advances in silicon photonics, thanks to their potentiality for the development of integrated silicon-based nanodevices.
Dottorato in Information and Communication Technologies, Ciclo XXXI
Keywords: Silicon; Photonics